2006
DOI: 10.1002/nur.20108
|View full text |Cite
|
Sign up to set email alerts
|

Testing a model of symptoms, communication, uncertainty, and well-being, in older breast cancer survivors

Abstract: Among older, long-term breast cancer survivors, symptoms from previous treatment can generate uncertainty about whether they represent co-morbid conditions, recurrence, or normal aging. This uncertainty can result in emotional distress and thoughts of recurrence. Communication with health care providers may help women reduce uncertainty and improve both emotional and cognitive well-being. To assess the influence of symptoms, uncertainty, and communication with providers on well-being, data from 203 Caucasian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
108
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 73 publications
7
108
1
1
Order By: Relevance
“…Using the information from this study, a core SCP document should include the content considered essential by patients, namely a diagnosis and treatment summary, information on lifestyle, nutrition, exercise, expected side effects, usual recovery, signs and symptoms of recurrence, a recommended follow-up schedule, knowledge of available support resources, and knowledge of information sent to primary care physician. It is encouraging that the essential SCP content identified by patients in our study, from varying age groups and rural/urban places of residence, largely concur with the IOM recommendations [8,11,[14][15][16][22][23][24]. This consistency suggests that these elements are a useful starting point in developing SCP content [2, 8-10, 13, 25].…”
Section: Discussion/backgroundsupporting
confidence: 78%
“…Using the information from this study, a core SCP document should include the content considered essential by patients, namely a diagnosis and treatment summary, information on lifestyle, nutrition, exercise, expected side effects, usual recovery, signs and symptoms of recurrence, a recommended follow-up schedule, knowledge of available support resources, and knowledge of information sent to primary care physician. It is encouraging that the essential SCP content identified by patients in our study, from varying age groups and rural/urban places of residence, largely concur with the IOM recommendations [8,11,[14][15][16][22][23][24]. This consistency suggests that these elements are a useful starting point in developing SCP content [2, 8-10, 13, 25].…”
Section: Discussion/backgroundsupporting
confidence: 78%
“…They would be expected to have more uncertainty because they lack any experiential frame of reference to define illness-related events. 43 In addition, the low educational level of the sample in this study may have contributed to greater uncertainty 35 ; less than 20% of our sample had more than a high school education. Moreover, many of our participants (77.4%) had family income of less than 4000 Yuan per month (US$658, €479), which is far below the average medical expense for inpatients in third-level hospitals (10 442.4 Yuan in 2010).…”
Section: Mediating Effect Of Self-efficacymentioning
confidence: 98%
“…According to Clayton et al, 39 when individuals lack sufficient information to form a cognitive schema, or representation, of an illness-related event, the event may be perceived as threatening and may result in increased emotional distress and disruption of well-being. These authors 39 suggested that effective communication with health care providers can reduce uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…These authors 39 suggested that effective communication with health care providers can reduce uncertainty. Decreasing uncertainty is particularly important as patients and their families begin to gain confidence in their ability to manage the VADs.…”
Section: Discussionmentioning
confidence: 99%